Fipronil resistance in pink stem borer, Sesamia inferens (Walker) (Lepidoptera: Noctuidae) from Pakistan: Cross-resistance, genetics and realized heritability. (June 2019) - Mansoor, Muhammad Mudassir; Raza, Abu Bakar Muhammad; Afzal, Muhammad Babar Shahzad
Abstract: Pink stem borer Sesamia inferens (Walker) (Lepidoptera: Noctuidae) is a major pest of sugarcane and rice frequently controlled by the use of insecticides, including fipronil. This study focused on fipronil resistance characterization in S. inferens by selecting a population (called Fipro-SEL Pop) with fipronil for 14 generations. Fipro-SEL Pop population showed 106.00- and 22.71-fold resistance to fipronil when compared to unselected (UNSEL) and Field strains, respectively. Fipro-SEL strain showed no cross-resistance to chlorpyrifos, lambda-cyhalothrin and spinosad. Reciprocal crosses between Fipro-SEL and UNSEL strains revealed an autosomal and incompletely recessive nature of resistance to fipronil. The F1 and F1 ' showed similar LC50 values against fipronil and their dominance values were 0.46 and 0.53, respectively. Chi-square goodness of fit test suggested that fipronil resistance was polygenic. Realized heritability value was 0.25 for fipronil resistance. These outcomes would be useful for effective management of S. inferens . Highlights: Sesamia inferens showed 106- and 22.71-fold resistance to fipronil when compared to UNSEL and Field strains. Fipro-SEL strain showed no cross-resistance to other tested insecticides. Resistance to fipronil in Sesamia inferens was autosomal, incompletely recessive and polygenic. Realized heritability ( h 2 ) value was 0.25.